Career growth of a public servant in the conditions of modernization of public administration in Ukraine - T.V.; Т.А. (Економіка, управління та адміністрування)
The article provides a scientific and theoretical analysis of public servant career as an administrative and legal category, identifies areas of public service development in terms of public administration reform in Ukraine. The current state and problems of modernization of public service and human resources management are analyzed in accordance with European standards, where the priority areas are modernization of public service and human resources management. The paper studies new approaches and tools for public service, defined by the reform strategy in Ukraine, this allows us to note that the innovations provided by the draft law of Ukraine «On Public Service» are more in line with modern challenges.